Music and the Line of Most Resistance - Schnabel, Artur 1882-1951; Matheson, Lynn; Mottier, Ann Schnabel (Hofheim Wolke Verlag, 2007)
Music and the Line of Most Resistance The title of three lectures Schnabel gave in 1940 at the University of Chicago exemplifies his conviction that the realization of musical masterpieces prompts us to not only overcome, but even actively seek difficulties. To him, the highest form of music is characterized by the fact that it can never be performed truly adequately, that every interpretation is merely an approximation of an unattainable ideal. Generations of musicians keep returning to the same key works in the Western classical repertoire. With the true musical masterpieces, this is a never-ending process.
Keywords: Music criticism